Legal Dynamics Of Land Digitalization In The Electronic Land Registration System - Tommy Leonard; Niko Demus Simarmata (Unissula, 2023)
The purpose of this study is to examine and analyze legal arrangements for land registration in accordance with the concepts and constraints in implementing land digitization. The analysis in this study uses a qualitative descriptive research method with primary and secondary legal data sources, namely looking at implementation and compliance with current regulations. The object of the research was conducted at the Deli Serdang Regency Land Office as one of the land offices that has the most services in Indonesia. The results of the research from this paper are that the regulation of online clean check services and electronic mortgage rights has not been specifically regulated in an implementing regulation but rather a computerized system implemented by automating procedures that were previously manual. Then the implementation concept is carried out based on the ATR/BPN ministerial policy related to the implementation of electronic certificates. In its implementation, there are 2 (two) obstacles, namely internal constraints and external constraints.